Pet sematary. Bloodlines [videorecording (DVD)] - Beer, Lindsey Anderson; Buhler, Jeff, 1967-; White, Jackson, 1996-; Goodluck, Forrest, 1998-; Mulhern, Jack; Thomas, Henry, 1971-; Lind, Natalie Alyn, 1999-; LaBlanc, Isabella Star; Grier, Pam, 1949-; Duchovny, David; King, Stephen, 1947- (Paramount, 2023)
In 1969, a young Jud Crandall dreams of leaving his hometown of Ludlow, Maine behind, but soon discovers sinister secrets buried within and is forced to confront a dark family history that will forever keep him connected to Ludlow. Banding together, Jud and his childhood friends must fight an ancient evil that has gripped Ludlow since its founding, and once unearthed has the power to destroy everything in its path. Based on the untold chapter from Pet Sematary, Stephen King's chilling novel, is a terrifying prequel and the untold story of why sometimes dead is better.